Surface sizing agent for papermaking and preparation method thereof

By using cationic starch, modified nanosilicon dioxide, modified nanocellulose and other components in the surface glue sizing agent for papermaking, a thin film is formed, which solves the problem of poor performance of existing surface glue sizing agent for papermaking, and realizes the The paper has improved efficient water resistance, antibacterial and oil resistance, improving printing quality and reducing costs.

CN119411425APending Publication Date: 2025-02-11DONGGUAN WEILONG CHEMICAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411542137.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing surface glue sizing agents for papermaking have poor performance, resulting in insufficient water resistance and oil resistance of the paper, low surface strength and smoothness, large amount of use, high cost, and insufficient comprehensive effect.

Method used

A surface glue sizing agent for papermaking is adopted, including cationic starch, modified nanosilica, modified nanocellulose, styrene, cationic acrylate monomer, hydroxyethyl acrylate, cationic emulsifier, antibacterial agent and initiator The solution, carefully selected and proportioned raw materials, forms a thin film to improve the water resistance, antibacterial and oil resistance of the paper.

Benefits of technology

It significantly improves the water resistance, antibacterial and oil resistance of paper, enhances surface strength and smoothness, improves printing quality, reduces usage and costs, and is in line with the trend of environmental protection and sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005113026850000091
    Figure BDA0005113026850000091
  • Figure BDA0005113026850000101
    Figure BDA0005113026850000101
Patent Text Reader

Abstract

The invention relates to the technical field of paper surface treating agents, in particular to a surface sizing agent for papermaking and a preparation method thereof. The invention relates to a surface sizing agent for papermaking. Comprising the following preparation raw materials: 48-52 parts of cationic starch, 2-2.5 parts of modified nano silicon dioxide, 5-6 parts of modified nano cellulose, 50-55 parts of styrene, 48-55 parts of a cationic acrylate monomer, 6-7 parts of hydroxyethyl acrylate, 5-6 parts of a cationic emulsifier, 4.5-5.0 parts of an antibacterial agent, 4-5 parts of an initiator solution with the mass concentration of 4%, and 450-480 parts of water, the antibacterial agent is chitosan modified cortex phellodendri powder. The surface sizing agent disclosed by the invention has the advantages of environment friendliness, economy and the like while improving the performance of paper, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of paper surface treatment agents, and in particular to a surface sizing agent for papermaking and a preparation method thereof. Background Art

[0002] In the modern papermaking industry, with the development of paper coating technology, we have put forward higher requirements for coating pigment additives. The coating not only protects the value of the coated object, but also plays a good decorative role due to its rich colors. Nowadays, with the continuous improvement of people's environmental awareness, the development of water-based coatings has been strongly advocated, and the solid components in the coating, such as pigments and fillers, occupy an important part.

[0003] The main components of conventional paper and paperboard are plant fibers, and such fibers have good hygroscopicity. Since the narrow gaps between the fibers in wet paper act as capillary attraction for water, untreated paper easily absorbs moisture. Therefore, sizing has become an indispensable process in the papermaking production process. By adding sizing agents and processing pulp, paper sheets or paperboard under certain process conditions, the purpose is to form a hydrophobic protective film on the surface of the paper, which plays a role in water resistance and reduces the hydrophilicity of plant fibers. At present, the development direction of paper in the market, especially the development of corrugated paper and board paper, has more and more serious problems, which are mainly reflected in the reduction of gram weight, deterioration of pulp quality, and unstable quality of internal sizing paper. Therefore, an excellent paper surface sizing agent is needed to protect and control the water resistance and oil resistance of the finished paper, improve the strength of the paper and have the performance of rapid maturation. At present, there are many types of sizing agents on the market, with poor performance, large dosage, high cost, and insufficient overall effect. Summary of the invention

[0004] The purpose of the present application is to provide a surface sizing agent for papermaking and a preparation method thereof in view of the deficiencies in the current technology. The surface sizing agent for papermaking prepared in the present application forms a thin film on the surface of paper, which can make the paper have better water resistance, antibacterial properties and oil resistance, while improving the surface strength and smoothness of the paper, improving printing quality, and requiring less usage and low cost.

[0005] In the first aspect, the present application provides a surface sizing agent for papermaking, which adopts the following technical solution: A surface sizing agent for papermaking comprises the following raw materials by weight: 48-52 parts of cationic starch, 2-2.5 parts of modified nano silicon dioxide, 5-6 parts of modified nano cellulose, 50-55 parts of styrene, 48-55 parts of cationic acrylate monomer, 6-7 parts of hydroxyethyl acrylate, 5-6 parts of cationic emulsifier, 4.5-5.0 parts of antibacterial agent, 4-5 parts of initiator solution with a mass concentration of 4%, and 450-480 parts of water, wherein the antibacterial agent is chitosan-modified phellodendron powder.

[0006] By adopting the above technical scheme, the surface sizing agent for papermaking of the present application achieves a comprehensive improvement in paper performance by carefully selecting and proportioning various raw materials. Cationic starch is one of the basic materials. Cationic starch can improve the surface strength and smoothness of paper, providing a good foundation for subsequent printing and other processing. Modified nano-silica: Through the coating modification of chitosan and sodium alginate, the hydrophobicity and dispersibility of nano-silica are improved, the water resistance and oil resistance of the surface sizing agent are enhanced, and the surface strength of the paper is improved. Modified nanocellulose: 2,2-difluoroethylamine is used for modification, and the fluorine element is introduced, which significantly improves the water resistance and oil resistance of the surface sizing agent, and at the same time improves the surface strength of the paper. Styrene: Copolymerization with other monomers to form a polymer with good film-forming and adhesion properties helps to improve the overall performance of the paper. Cationic acrylate monomer: Compounded with cationic starch, it significantly improves the surface strength of the paper and enhances the durability and stability of the paper. Hydroxyethyl acrylate: As a cross-linking agent, it can promote the cross-linking reaction between polymers and improve the durability and stability of the coating. Cationic emulsifier: helps the components to mix and disperse better, ensuring the stability and uniformity of the sizing agent. Antimicrobial agent (chitosan-modified Phellodendron powder): uses chitosan to modify Phellodendron powder to improve its dispersibility and compatibility, increase its antibacterial properties, and further improve the mechanical properties of the surface sizing agent. Initiator solution (mass concentration of 4%): used to initiate the polymerization reaction to ensure that each monomer can effectively polymerize to form the required polymer structure. Water: as a solvent, used to adjust the viscosity and fluidity of the sizing agent to ensure a smooth sizing process. The synergistic effect of these ingredients makes the final surface sizing agent for papermaking not only have a good sizing effect, but also can significantly improve the surface strength, water resistance, antibacterial and oil resistance of paper, while improving printing quality, reducing dosage and reducing costs.

[0007] Preferably, the preparation method of chitosan-modified Phellodendron chinense powder is as follows: add 20g chitosan to 200ml acetic acid solution with a mass concentration of 3%, stir and dissolve to obtain a chitosan solution; add 70g tannic acid to 500ml methanol, stir and dissolve to obtain a tannic acid solution; adjust the temperature of the chitosan solution to 36°C, add the tannic acid solution, 50g Phellodendron chinense powder and 6g N-hydroxysuccinimide while stirring, stir and react for 24h, and after the reaction is completed, dialyze and freeze-dry to obtain chitosan-modified Phellodendron chinense powder.

[0008] By adopting the above technical scheme, the cork powder itself has a certain antibacterial property, and chitosan, as a natural antibacterial material, can further enhance this property. Modifying the cork powder with chitosan can significantly improve the antibacterial properties of the surface sizing agent, which is of great significance for preventing microbial contamination and extending the service life of paper during papermaking. Chitosan is wrapped on the surface of the cork powder, which can promote the dispersibility and compatibility of the cork powder in the surface sizing agent, making its distribution more uniform. This not only helps to improve the overall quality of the paper, but also ensures the uniformity of the antibacterial effect. The cork powder modified with chitosan not only maintains the original antibacterial properties, but also may enhance the mechanical properties of the surface sizing agent through interaction with chitosan. This means that after surface treatment, the antibacterial properties of the paper are not only improved, but also its physical strength is enhanced. Chitosan-modified cork powder works together with other ingredients such as cationic starch and modified nano-silica to form a synergistic system. This synergistic effect is not only reflected in the improvement of antibacterial properties, but also includes the overall improvement of paper water resistance, oil resistance, surface strength and smoothness. As a renewable resource, the use of chitosan is in line with the current trend of environmental protection and sustainable development. By modifying the cortex phellodendri powder with chitosan, the surface sizing agent of the present application not only improves the performance of paper, but also reflects the pursuit of environmental friendliness and efficient use of resources. In summary, the chitosan-modified cortex phellodendri powder in the present application not only acts as an antibacterial agent, but also comprehensively improves the performance of the surface sizing agent for papermaking through synergistic effects with other ingredients, bringing significant advantages to the production and application of paper.

[0009] Preferably, the preparation method of the cationic starch is as follows: weigh 30g corn starch, add 120mL distilled water and stir evenly, ultrasonically treat for 30min, wash with distilled water, filter and dry to obtain starch; prepare the starch into 0.4g / mL starch paste, add 4.75g 3-chloro-2-hydroxypropyltrimethylammonium chloride and 3.25g sodium sulfate and stir evenly, put it in a constant temperature water bath at 40°C, adjust the pH value of the solution to 11, react for 8h, and adjust the pH value of the solution to 7; centrifuge and wash, dry in a 50°C drying oven for 24h, and grind to obtain cationic starch.

[0010] By adopting the above technical scheme, the prepared cationic starch can significantly improve the surface strength of paper. This is because cationic starch has good film-forming and adhesion properties, and can form a tough film on the surface of paper, thereby improving the tensile strength and folding resistance of paper. After cationic starch is compounded with cationic acrylate monomers, the water resistance of paper can be significantly improved. The hydrophilic groups of cationic starch interact with the negative charges on the fiber surface, enhancing the resistance of paper to moisture. The film formed by cationic starch on the surface of paper is not only tough, but also has high smoothness, which helps to improve the printing suitability of paper and improve the quality of printed products. Cationic starch works together with other components such as modified nano-silica and modified nano-cellulose to further improve the comprehensive performance of the surface sizing agent. For example, modified nano-silica improves water resistance and oil resistance, while modified nano-cellulose enhances water resistance and surface strength. The synergistic effect between these components makes the surface sizing agent perform well in improving paper performance. In summary, the main role of cationic starch in this application is to improve the surface strength of paper, improve smoothness and enhance water resistance. At the same time, it works synergistically with other components to further enhance the comprehensive performance of the surface sizing agent.

[0011] Preferably, the preparation method of the modified nano-silica is as follows: 100 ml of a nano-silica dispersion with a concentration of 0.25 g / ml and 10 ml of a chitosan solution with a concentration of 0.05 g / ml are mixed in a piston intermittent high-pressure homogenizer, first circulated 10 times at a pressure of 200 bar, then circulated 50 times at a pressure of 500 bar, then added to 15 ml of a sodium alginate solution with a concentration of 0.025 g / m and continued to circulate 10 times at a pressure of 200 bar, then circulated 50 times at a pressure of 500 bar, finally the obtained mixed solution is added dropwise to 500 mL of a calcium chloride solution with a concentration of 0.05 g / ml, and the cross-linking reaction is stirred at room temperature and 4000 rpm for 25 minutes. After the reaction is completed, it is filtered and dried to obtain the modified nano-silica.

[0012] By adopting the above technical scheme, the prepared modified nano-silica is modified by coating with chitosan and sodium alginate, which effectively improves the hydrophobicity and dispersibility of nano-silica, thereby improving the water resistance and oil resistance of the surface sizing agent. The modified nano-silica can significantly improve the surface strength of paper, so that the paper has better physical properties. The use of modified nano-silica in combination with other ingredients such as cationic starch, cationic acrylate monomers, etc. can produce a synergistic effect and further improve the overall performance of the surface sizing agent. In summary, the modified nano-silica in this application not only improves the water resistance and oil resistance of paper, but also enhances the surface strength of paper, and promotes synergy with other ingredients, thereby improving the comprehensive performance of the surface sizing agent.

[0013] Preferably, the preparation method of the cationic acrylate monomer is as follows: 500 g of isopropanol and 151.6 g of trimethylammonium chloride glycidyl ether are added to a reactor equipped with a stirrer, a thermometer and a dropping funnel, and the mixture is stirred evenly, and then 79.2 g of acrylic acid monomer is added dropwise through the dropping funnel, and then 2.1 g of triethylamine is added, and then the temperature is raised to 70° C. and the reaction is carried out for 10 hours, and the product is washed with tetrahydrofuran for 3 hours to obtain a cationic acrylate monomer.

[0014] Preferably, the method for preparing the modified nanocellulose comprises the following steps: S61, adding water to 10 g of nanocellulose to prepare a 1.5% nanocellulose aqueous suspension, and then evaporating the suspension to make it gel-like, thereby obtaining gel-like nanocellulose; S62, 3 g of N-N-dimethylformamide and gel-like nanocellulose were mixed evenly, and then stirred at a constant temperature of 85° C. for 5 h, and then 400 g of trifluoroacetic anhydride and 20 g of 4-dimethylaminopyridine were added, and then stirred for 30 min, and the temperature was raised to 100° C., reacted for 6 h, and then cooled for 30 min, and then washed with ethanol, acetone and deionized water to obtain esterified modified nanocellulose; S63. Evenly mix 100 g of esterified modified nanocellulose, 60 g of 2,2-difluoroethylamine and 500 mL of N-N-dimethylformamide, adjust the pH to neutral with sodium hydroxide and hydrochloric acid, place in an oil bath at 70°C, and stir at 600 rpm for 12 hours. After the reaction is completed, centrifuge and wash several times until the modified nanocellulose is separated. Centrifuge and wash three times with ethanol to remove unreacted amine, and then perform dialysis membrane treatment on the suspension to obtain modified nanocellulose.

[0015] By adopting the above technical scheme, firstly, water is added to nanocellulose to prepare gel nanocellulose; secondly, the gel nanocellulose is mixed with N,N-dimethylformamide and esterified; finally, the esterified modified nanocellulose is reacted with 2,2-difluoroethylamine to obtain the final product. The prepared modified nanocellulose can significantly improve the water resistance and oil resistance of the surface sizing agent, and at the same time improve the surface strength of the paper.

[0016] Preferably, the cationic emulsifier is prepared by mixing dimethylaminopropyl methacrylamide, hexadecyltrimethylammonium chloride and polydiallylmethylammonium chloride in a mass ratio of 3:2:3.

[0017] By adopting the above technical scheme, the cationic emulsifier can evenly mix the oil-soluble components (such as styrene, hydroxyethyl acrylate, etc.) with the aqueous phase to form a stable emulsion. This can ensure that the components are evenly distributed when coated on the paper surface, thereby improving the uniformity and stability of the sizing agent. Since the cationic emulsifier has a positive charge, it can interact with the negative charge on the surface of the paper to enhance the adhesion between the sizing agent and the paper, thereby improving the sizing effect. The use of cationic emulsifiers helps to improve the surface strength and smoothness of the paper, which is very important for improving printing quality. When the three compounds of dimethylaminopropyl methacrylamide, hexadecyltrimethylammonium chloride and polydiallylmethylammonium chloride are mixed, there is a synergistic effect. This synergistic effect may include: the mixed use of cationic surfactants of different structures may show better emulsification effects under different conditions. By adjusting the ratio of different compounds, the charge density of the emulsifier can be optimized to adapt to different paper surface characteristics. The composite emulsifier may help to form a more uniform and stable protective film, thereby providing better water resistance and oil resistance. In summary, cationic emulsifiers not only play a role in emulsification and dispersion, but also enhance the interaction with the paper surface through their unique cationic properties, thus improving the sizing effect. At the same time, through the synergistic effect of three different compounds, the overall performance of the sizing agent can be further optimized, making it more suitable for high-quality paper production needs.

[0018] Preferably, the initiator solution with a mass concentration of 4% is an aqueous solution of ammonium persulfate with a mass concentration of 4%.

[0019] In a second aspect, the present application provides a method for preparing a surface sizing agent for papermaking, which adopts the following technical scheme: As a general technical concept, the present application also provides a method for preparing the above-mentioned surface sizing agent for papermaking, comprising the following steps: S91, adding water and cationic starch to a reactor according to mass fractions, stirring and heating to 6570°C, keeping warm and stirring for 10 minutes, then sequentially adding modified nano-silica, modified nano-cellulose, styrene, cationic acrylate monomer, hydroxyethyl acrylate and cationic emulsifier to the reactor and stirring for 90 minutes, then heating to 88°C, and then slowly dripping a 4% initiator solution into the reactor, the dripping time is 60 minutes, after the dripping is completed, keeping warm and reacting for 90 minutes to obtain material A; S92, cooling material A to 40° C., then adding an antibacterial agent and stirring for 20 minutes to obtain a surface sizing agent for papermaking.

[0020] In summary, the beneficial technical effects of this application are: 1. Improve the water and oil resistance of paper: By using modified nano-silica and modified nano-cellulose, as well as compounding cationic starch and cationic acrylate monomers, the water and oil resistance of the surface sizing agent are significantly improved. This makes the paper less likely to be penetrated when it comes into contact with water or oil, maintaining its original performance.

[0021] 2. Enhanced antibacterial properties: Using chitosan to modify Phellodendron chinense powder as an antibacterial agent not only increases the antibacterial properties, but also improves the mechanical properties of the surface sizing agent. Chitosan is wrapped on the surface of Phellodendron chinense powder, which promotes the dispersibility and compatibility of Phellodendron chinense powder, making its distribution more uniform and enhancing the antibacterial effect of paper.

[0022] 3. Improve the surface strength and smoothness of paper: Cationic starch and cationic acrylate monomers can significantly improve the surface strength of paper. The modified nanocellulose introduces fluorine elements, which further improves the mechanical properties of the surface sizing agent, making the paper stronger and more durable. At the same time, the surface sizing agent forms a thin film on the surface of the paper, which improves the smoothness of the paper and helps to improve the printing quality.

[0023] 4. Small amount and low cost: Due to the superior performance of the surface sizing agent, the amount required for use is small, thus reducing the production cost. This is of great significance for large-scale production and application.

[0024] 5. Environmentally friendly: The materials used in this application, such as chitosan, sodium alginate, etc., are of natural origin, environmentally friendly, and in line with the principles of green chemistry. DETAILED DESCRIPTION

[0025] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0026] In the following examples and preparation examples, 1 part means 100 g.

[0027] Preparation Example 1 Preparation of Chitosan-modified Cortex Phellodendri Powder The preparation method of chitosan-modified Phellodendron chinense powder is as follows: adding 20g of chitosan to 200ml of acetic acid solution with a mass concentration of 3%, stirring and dissolving to obtain a chitosan solution; adding 70g of tannic acid to 500ml of methanol, stirring and dissolving to obtain a tannic acid solution; adjusting the temperature of the chitosan solution to 36°C, adding the tannic acid solution, 50g of Phellodendron chinense powder and 6g of N-hydroxysuccinimide while stirring, stirring and reacting for 24h, and after the reaction is completed, dialyzing and freeze-drying to obtain the chitosan-modified Phellodendron chinense powder.

[0028] Preparation Example 2 Preparation of cationic starch The preparation method of cationic starch is as follows: weigh 30g corn starch, add 120mL distilled water and stir evenly, ultrasonically treat for 30min, wash with distilled water, filter and dry to obtain starch; prepare the starch into 0.4g / mL starch paste, add 4.75g 3-chloro-2-hydroxypropyltrimethylammonium chloride and 3.25g sodium sulfate and stir evenly, put into a constant temperature water bath at 40°C, adjust the pH value of the solution to 11, react for 8h, adjust the pH value of the solution to 7; centrifuge, wash, dry in a 50°C drying oven for 24h, grind and obtain cationic starch.

[0029] Preparation Example 3 Preparation of modified nano-silicon dioxide The preparation method of modified nano-silica is as follows: 100 ml of a nano-silica dispersion with a concentration of 0.25 g / ml and 10 ml of a chitosan solution with a concentration of 0.05 g / ml are mixed in a piston intermittent high-pressure homogenizer, first circulated 10 times at a pressure of 200 bar, then circulated 50 times at a pressure of 500 bar, then 15 ml of a sodium alginate solution with a concentration of 0.025 g / ml is added and continued to circulate 10 times at a pressure of 200 bar, then circulated 50 times at a pressure of 500 bar, finally the obtained mixed solution is added dropwise to 500 ml of a calcium chloride solution with a concentration of 0.05 g / ml, and the cross-linking reaction is stirred at room temperature and 4000 rpm for 25 minutes. After the reaction is completed, it is filtered and dried to obtain modified nano-silica.

[0030] Preparation Example 4 Preparation of Cationic Acrylate Monomer The preparation method of the cationic acrylate monomer is as follows: 500 g of isopropanol and 151.6 g of trimethylammonium chloride glycidyl ether are added into a reactor equipped with a stirrer, a thermometer and a dropping funnel, and the mixture is stirred evenly, and then 79.2 g of acrylic acid monomer is added dropwise through the dropping funnel, and then 2.1 g of triethylamine is added, and then the temperature is raised to 70° C. and the reaction is carried out for 10 hours. The product is washed with tetrahydrofuran for 3 hours to obtain a cationic acrylate monomer.

[0031] Preparation Example 5 Preparation of modified nanocellulose The preparation method of modified nanocellulose comprises the following steps: S61, adding water to 10 g of nanocellulose to prepare a 1.5% nanocellulose aqueous suspension, and then evaporating the suspension to make it gel-like, thereby obtaining gel-like nanocellulose; S62, 3 g of N-N-dimethylformamide and gel-like nanocellulose were mixed evenly, and then stirred at a constant temperature of 85° C. for 5 h, and then 400 g of trifluoroacetic anhydride and 20 g of 4-dimethylaminopyridine were added, and then stirred for 30 min, and the temperature was raised to 100° C., reacted for 6 h, and then cooled for 30 min, and then washed with ethanol, acetone and deionized water to obtain esterified modified nanocellulose; S63. Evenly mix 100 g of esterified modified nanocellulose, 60 g of 2,2-difluoroethylamine and 500 mL of N-N-dimethylformamide, adjust the pH to neutral with sodium hydroxide and hydrochloric acid, place in an oil bath at 70°C, and stir at 600 rpm for 12 hours. After the reaction is completed, centrifuge and wash several times until the modified nanocellulose is separated. Centrifuge and wash three times with ethanol to remove unreacted amine, and then perform dialysis membrane treatment on the suspension to obtain modified nanocellulose.

[0032] Example 1 A surface sizing agent for papermaking comprises the following raw materials, measured by weight: 48 parts of cationic starch, 2 parts of modified nano silicon dioxide, 5 parts of modified nano cellulose, 50 parts of styrene, 48 parts of cationic acrylate monomer, 6 parts of hydroxyethyl acrylate, 5 parts of cationic emulsifier, 4.5 parts of antibacterial agent, 4 parts of 4% ammonium persulfate aqueous solution, and 450 parts of water, wherein the antibacterial agent is chitosan modified phellodendron powder, and the cationic emulsifier is prepared by mixing dimethylaminopropyl methacrylamide, hexadecyltrimethylammonium chloride and polydiallylmethylammonium chloride in a weight ratio of 3:2:3.

[0033] The preparation method of the surface sizing agent for papermaking comprises the following steps: S91. Add water and cationic starch to the reactor according to the mass fractions, stir and heat to 65°C, keep warm and stir for 10 minutes, then add modified nano-silica, modified nano-cellulose, styrene, cationic acrylate monomer, hydroxyethyl acrylate and cationic emulsifier to the reactor in sequence and stir for 90 minutes, then heat to 88°C, and then slowly drop a 4% ammonium persulfate aqueous solution into the reactor for 60 minutes. After the dropwise addition is completed, keep warm and react for 90 minutes to obtain material A; S92, cooling material A to 40° C., then adding an antibacterial agent and stirring for 20 minutes to obtain a surface sizing agent for papermaking.

[0034] Example 2 A surface sizing agent for papermaking comprises the following raw materials, measured by weight: 52 parts of cationic starch, 2.5 parts of modified nano silicon dioxide, 6 parts of modified nano cellulose, 55 parts of styrene, 55 parts of cationic acrylate monomer, 7 parts of hydroxyethyl acrylate, 6 parts of cationic emulsifier, 5.0 parts of antibacterial agent, 5 parts of 4% ammonium persulfate aqueous solution, and 480 parts of water, wherein the antibacterial agent is chitosan modified phellodendron powder, and the cationic emulsifier is prepared by mixing dimethylaminopropyl methacrylamide, hexadecyltrimethylammonium chloride and polydiallylmethylammonium chloride in a weight ratio of 3:2:3.

[0035] The preparation method of the surface sizing agent for papermaking comprises the following steps: S91. Add water and cationic starch to the reactor according to the mass fractions, stir and heat to 70°C, keep warm and stir for 10 minutes, then add modified nano-silica, modified nano-cellulose, styrene, cationic acrylate monomer, hydroxyethyl acrylate and cationic emulsifier to the reactor in sequence and stir for 90 minutes, then heat to 88°C, and then slowly drop a 4% ammonium persulfate aqueous solution into the reactor for 60 minutes. After the dropwise addition is completed, keep warm and react for 90 minutes to obtain material A; S92, cooling material A to 40° C., then adding an antibacterial agent and stirring for 20 minutes to obtain a surface sizing agent for papermaking.

[0036] Example 3 A surface sizing agent for papermaking comprises the following raw materials, measured by weight: 50 parts of cationic starch, 2.3 parts of modified nano silicon dioxide, 5.5 parts of modified nano cellulose, 53 parts of styrene, 52 parts of cationic acrylate monomer, 6.5 parts of hydroxyethyl acrylate, 5.5 parts of cationic emulsifier, 4.8 parts of antibacterial agent, 4.5 parts of 4% ammonium persulfate aqueous solution, and 460 parts of water, wherein the antibacterial agent is chitosan modified phellodendron powder, and the cationic emulsifier is prepared by mixing dimethylaminopropyl methacrylamide, hexadecyltrimethylammonium chloride and polydiallylmethylammonium chloride in a weight ratio of 3:2:3.

[0037] The preparation method of the surface sizing agent for papermaking comprises the following steps: S91. Add water and cationic starch to the reactor according to the mass fractions, stir and heat to 68°C, keep warm and stir for 10 minutes, then sequentially add modified nano-silica, modified nano-cellulose, styrene, cationic acrylate monomer, hydroxyethyl acrylate and cationic emulsifier to the reactor and stir for 90 minutes, then heat to 88°C, and then slowly drop a 4% ammonium persulfate aqueous solution into the reactor for 60 minutes. After the dropwise addition is completed, keep warm and react for 90 minutes to obtain material A; S92, cooling material A to 40° C., then adding an antibacterial agent and stirring for 20 minutes to obtain a surface sizing agent for papermaking.

[0038] Comparative Example 1 The same as Example 3, except that an equal amount of nano silicon oxide is used instead of modified nano silicon dioxide.

[0039] Comparative Example 2 Same as Example 3, except that an equal amount of nanocellulose is used instead of modified nanocellulose.

[0040] Comparative Example 3 The same as Example 3, except that an equal amount of Phellodendron chinense powder is used instead of chitosan-modified Phellodendron chinense powder.

[0041] Comparative Example 4 The same as Example 3, except that the cationic emulsifier is dimethylaminopropyl methacrylamide.

[0042] Comparative Example 5 The same as Example 3, except that the cationic emulsifier is hexadecyltrimethylammonium chloride.

[0043] Comparative Example 6 The same as Example 3, except that the cationic emulsifier is polydiallylmethylammonium chloride.

[0044] Performance Testing Preparation of the evaluation formula for the application of paper surface sizing agent: add 85g of starch to 415g of water, and add 0.1g of amylase, put them into a beaker and stir, heat to 98°C in a water bath, stir and keep warm for 30 minutes, cool down to obtain cooked starch, take 100g of cooked starch, add 0.5g of paper surface sizing agent, stir for 20 minutes, apply with No. 2 coating rod, and evenly apply it on the un-sizing corrugated core paper at a speed of 15m / min, dry in an oven at 90°C for 40 seconds, and start testing.

[0045] Using the above method, the surface sizing agents for papermaking prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were compared and tested by the following experiments. The test results are shown in Table 1.

[0046] Glue application amount: Test the paper Cobb value of the sample according to GB / T1540-2002. The smaller the Cobb value Cobb60 is, the more glue is applied and the better the water resistance is. The surface strength was measured using the J-IGT350 IGT printing adaptor; Contact angle: According to the method of ASTM D 724-1999 (2003), the water contact angle of the paper surface was tested using a wetting angle tester; the test medium was replaced with paraffin oil, and the paraffin oil contact angle of the paper surface was tested; Antibacterial performance: Staphylococcus aureus was selected as the experimental object in this experiment. The corrugated paper coated with each group of samples was cut into 1cm×1cm samples. Staphylococcus aureus was activated and prepared into a concentration of 1×10 6 cfu / mL of bacterial suspension, and then put the cut sample in. Fix the conical flask containing the bacterial suspension and sample on an oscillating shaker, shake at 300 rpm for 2 minutes at 20-25°C, and then take 1.0mL of the bacterial suspension and dilute it to 100 times. Take 1.0mL after shaking, inoculate it on the agar base, and culture it at 37°C for 48 hours under natural light, then count it using the method in GB15979-2003 and calculate the inhibition rate.

[0047] Table 1 Performance test Analyzing the data in Table 1, we can see that: 1) The surface sizing agent for papermaking prepared in Examples 1 to 3 forms a thin film on the surface of paper, which can make the paper have better water resistance, antibacterial properties and oil resistance, while increasing the surface strength of the paper and improving the printing quality.

[0048] 2) The performance comparison analysis of the surface sizing agent for papermaking prepared in combination with Example 3 and Comparative Example 1 shows that the prepared modified nano-silicon dioxide is modified by coating with chitosan and sodium alginate, which effectively improves the hydrophobicity and dispersibility of nano-silicon oxide, thereby improving the water resistance and oil resistance of the surface sizing agent. The modified nano-silicon dioxide can significantly improve the surface strength of paper and make the paper have better physical properties. The use of modified nano-silicon dioxide in combination with other ingredients such as cationic starch, cationic acrylate monomers, etc. can produce a synergistic effect and further improve the overall performance of the surface sizing agent.

[0049] 3) The comparative analysis of the performance of the surface sizing agent for papermaking prepared in combination with Example 3 and Comparative Example 2 shows that the modified nanocellulose prepared in the present application is 2,2-difluoroethylamine-modified nanocellulose, and the introduction of fluorine element can significantly improve the water resistance and oil resistance of the surface sizing agent, while improving the surface strength of the paper.

[0050] 4) The comparative analysis of the performance of the surface sizing agent for papermaking prepared in combination with Example 3 and Comparative Example 3 shows that Phellodendron powder itself has certain antibacterial properties, and chitosan, as a natural antibacterial material, can further enhance this property. Modifying Phellodendron powder by chitosan can significantly improve the antibacterial properties of the surface sizing agent, which is of great significance for preventing microbial contamination and extending the service life of paper during the papermaking process. Chitosan is wrapped on the surface of Phellodendron powder, which can promote the dispersibility and compatibility of Phellodendron powder in the surface sizing agent and make its distribution more uniform. This not only helps to improve the overall quality of the paper, but also ensures the uniformity of the antibacterial effect. The chitosan-modified Phellodendron powder not only maintains the original antibacterial properties, but also may enhance the mechanical properties of the surface sizing agent through interaction with chitosan.

[0051] 5) The performance comparison analysis of the surface sizing agent for papermaking prepared in combination with Example 3 and Comparative Examples 4-6 shows that the cationic emulsifier is prepared by mixing dimethylaminopropyl methacrylamide, hexadecyl trimethyl ammonium chloride and polydiallyl methyl ammonium chloride in a mass ratio of 3:2:3. The cationic emulsifier can evenly mix the oil-soluble components (such as styrene, hydroxyethyl acrylate, etc.) with the aqueous phase to form a stable emulsion. This can ensure that the components are evenly distributed when coated on the surface of the paper, and improve the uniformity and stability of the sizing agent. Since the cationic emulsifier has a positive charge, it can interact with the negative charge on the surface of the paper to enhance the adhesion between the sizing agent and the paper, thereby improving the sizing effect. The use of cationic emulsifier helps to improve the surface strength and smoothness of the paper, which is very important for improving the printing quality. When the three compounds of dimethylaminopropyl methacrylamide, hexadecyl trimethyl ammonium chloride and polydiallyl methyl ammonium chloride are used in combination, there is a synergistic effect. This synergistic effect may include: the mixed use of cationic surfactants of different structures may show better emulsification effects under different conditions. By adjusting the ratio of different compounds, the charge density of the emulsifier can be optimized to suit different paper surface characteristics. Composite emulsifiers may help form a more uniform and stable protective film, thereby providing better water and oil resistance.

[0052] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.

Claims

1. A surface sizing agent for papermaking, characterized in that: The preparation raw materials include the following in parts by mass: 48-52 parts of cationic starch, 2-2.5 parts of modified nano-silicon dioxide, 5-6 parts of modified nano-cellulose, 50-55 parts of styrene, 48-55 parts of cationic acrylate monomer, 6-7 parts of hydroxyethyl acrylate, 5-6 parts of cationic emulsifier, 4.5-5.0 parts of antibacterial agent, 4-5 parts of 4% initiator solution by mass concentration, and 450-480 parts of water, wherein the antibacterial agent is chitosan modified phellodendron powder.

2. A surface sizing agent for papermaking according to claim 1, characterized in that: The preparation method of chitosan-modified Phellodendron chinense powder is as follows: adding 20g of chitosan to 200ml of acetic acid solution with a mass concentration of 3%, stirring and dissolving to obtain a chitosan solution; adding 70g of tannic acid to 500ml of methanol, stirring and dissolving to obtain a tannic acid solution; adjusting the temperature of the chitosan solution to 36°C, adding the tannic acid solution, 50g of Phellodendron chinense powder and 6g of N-hydroxysuccinimide while stirring, stirring and reacting for 24h, and after the reaction is completed, dialyzing and freeze-drying to obtain the chitosan-modified Phellodendron chinense powder.

3. A surface sizing agent for papermaking according to claim 1, characterized in that: The preparation method of the cationic starch is as follows: weigh 30g corn starch, add 120mL distilled water and stir evenly, ultrasonically treat for 30min, wash with distilled water, filter and dry to obtain starch; prepare the starch into 0.4g / mL starch paste, add 4.75g 3-chloro-2-hydroxypropyltrimethylammonium chloride and 3.25g sodium sulfate and stir evenly, put into a constant temperature water bath at 40°C, adjust the pH value of the solution to 11, react for 8h, and adjust the pH value of the solution to 7; centrifuge, wash, dry in a drying oven at 50°C for 24h, grind and obtain the cationic starch.

4. A surface sizing agent for papermaking according to claim 1, characterized in that: The preparation method of the modified nano silicon dioxide is as follows: 100 ml of a nano silicon oxide dispersion with a concentration of 0.25 g / ml and 10 ml of a chitosan solution with a concentration of 0.05 g / ml are mixed in a piston intermittent high-pressure homogenizer, firstly circulated 10 times at a pressure of 200 bar, then circulated 50 times at a pressure of 500 bar, then 15 ml of a sodium alginate solution with a concentration of 0.025 g / ml is added, and the mixture is further circulated 10 times at a pressure of 200 bar, and then circulated 50 times at a pressure of 500 bar, and finally the obtained mixed solution is added dropwise into 500 ml of a calcium chloride solution with a concentration of 0.05 g / ml, and a cross-linking reaction is carried out at room temperature and 4000 rpm for 25 minutes, and after the reaction is completed, the mixture is filtered and dried to obtain the modified nano silicon oxide.

5. A surface sizing agent for papermaking according to claim 1, characterized in that: The preparation method of the cationic acrylate monomer is as follows: 500g of isopropanol and 151.6g of trimethylammonium chloride glycidyl ether are added into a reactor equipped with a stirrer, a thermometer and a dropping funnel, and the mixture is stirred evenly, and then 79.2g of acrylic acid monomer is added dropwise through the dropping funnel, and then 2.1g of triethylamine is added, and then the temperature is raised to 70°C for reaction for 10h, and the product is washed with tetrahydrofuran for 3 hours to obtain the cationic acrylate monomer.

6. A surface sizing agent for papermaking according to claim 1, characterized in that: The preparation method of the modified nanocellulose comprises the following steps: S61, adding water to 10 g of nanocellulose to prepare a 1.5% nanocellulose aqueous suspension, and then evaporating the suspension to make it gel-like, thereby obtaining gel-like nanocellulose; S62, 3 g of N-N-dimethylformamide and gel-like nanocellulose were mixed evenly, and then stirred at a constant temperature of 85° C. for 5 h, and then 400 g of trifluoroacetic anhydride and 20 g of 4-dimethylaminopyridine were added, and then stirred for 30 min, and the temperature was raised to 100° C., reacted for 6 h, and then cooled for 30 min, and then washed with ethanol, acetone and deionized water to obtain esterified modified nanocellulose; S63. Evenly mix 100 g of esterified modified nanocellulose, 60 g of 2,2-difluoroethylamine and 500 mL of N-N-dimethylformamide, adjust the pH to neutral with sodium hydroxide and hydrochloric acid, place in an oil bath at 70°C, and stir at 600 rpm for 12 hours. After the reaction is completed, centrifuge and wash several times until the modified nanocellulose is separated. Centrifuge and wash three times with ethanol to remove unreacted amine, and then perform dialysis membrane treatment on the suspension to obtain modified nanocellulose.

7. A surface sizing agent for papermaking according to claim 1, characterized in that: The cationic emulsifier is prepared by mixing dimethylaminopropyl methacrylamide, hexadecyltrimethylammonium chloride and polydiallylmethylammonium chloride in a mass ratio of 3:2:

3.

8. A surface sizing agent for papermaking according to claim 1, characterized in that: The initiator solution with a mass concentration of 4% is an aqueous solution of ammonium persulfate with a mass concentration of 4%.

9. A method for preparing a surface sizing agent for papermaking according to any one of claims 1 to 8, comprising the following steps: S91. Add water and cationic starch to the reactor according to the mass fractions, stir and heat to 6570°C, keep warm and stir for 10 minutes, then add modified nano-silica, modified nano-cellulose, styrene, cationic acrylate monomer, hydroxyethyl acrylate and cationic emulsifier to the reactor in sequence and stir for 90 minutes, then heat to 88°C, and then slowly drop a 4% initiator solution into the reactor for 60 minutes. After the dropwise addition is completed, keep warm and react for 90 minutes to obtain material A; S92, cooling material A to 40° C., then adding an antibacterial agent and stirring for 20 minutes to obtain a surface sizing agent for papermaking.

Citation Information

Cited By

  • A fluorine-free environmentally friendly oil-proof agent for paper base and its preparation method and application

    CN119754087A